Reproductive aspects of brownstripe red snapper Lutjanus vitta (Quoy & Gainmard, 1824) in Jakarta Bay and its surroundings - Selvia Oktaviyani; Wanwan Kurniawan (Jurnal Iktiologi Indonesia, 2017)
Study on reproductive aspects of brownstripe red snapper Lutjanus vitta (Quoy & Gainmard, 1824) in Jakarta Bay and its surroundings can obtain important information for fish resources management. The objective of this research is to analyze length frequency distribution, sex ratio, gonadal maturation, gonado somatic index, the length at first maturity (Lm) and the average length of captured (Lc) for this fish. This research was conducted from April 2014 to January 2015 with sampling location in Tanjung Pasir Fishing Port, Tangerang. Fish sampling and of fish that were. The observed aspects included fork length, weight, sex, gonad maturity and gonad weight was done monthly. The result showed that the fork length of this fish ranged between 132-265 mm with the equal sex ratio. The capture fish are dominated by fish with immature stage. The highest of gonado somatic index was on September 2014 (2%). The fork length at first maturity (Lm) were 252 mm (male) and 187 mm (female) while the average fork length of captured (Lc) was 178 mm. This condition can cause a growth overfishing. Abstrak Kajian beberapa aspek reproduksi ikan kakap Lutjanus vitta (Quoy & Gainmard, 1824) di Teluk Jakarta dan sekitarnya dapat menghasilkan informasi yang sangat penting dalam rangka pengelolaan sumber daya ikan tersebut. Tujuan pene-litian ini adalah untuk menganalisis sebaran frekuensi panjang, nisbah kelamin, kematangan gonad, indeks kematangan gonad, ukuran kali pertama matang gonad, dan rata-rata panjang tertangkap ikan kakap. Penelitian dilaksanakan pada bulan April 2014 hingga Januari 2015 di Tempat Pelelangan Ikan (TPI) Tanjung Pasir, Tangerang. Aspek yang diamati meliputi panjang cagak dan bobot tubuh ikan, jenis kelamin, kematangan gonad, dan bobot gonad. Hasil penelitian me-nunjukkan bahwa ukuran panjang cagak ikan kakap berkisar antara 132-265 mm dengan nisbah kelamin dalam keadaan seimbang. Ikan kakap yang tertangkap didominasi oleh ikan yang belum matang gonad. Indeks kematangan gonad tertinggi terjadi pada bulan September 2014 yaitu 2%. Ukuran panjang cagak kali pertama ikan matang gonad (Lm) adalah 252 mm (jantan) dan 187 mm (betina), serta panjang cagak rata-rata tertangkap (Lc) adalah 178 mm. Kondisi ini dapat menyebabkan lebih-tangkap yang mengganggu tingkat pertumbuhan ikan kakap.